Validation of Antidiabetic Potential of Pterocarpus marsupium: An In Silico Approach - Khem Raj Joshi; Ravindra Khadka; Sandesh Poudel; Shankar Thapa; Iqrar Ahmad; Ammar A. Razzak Mahmood (Journal of Chemistry)
Diabetes mellitus is a metabolic syndrome and a global health burden that has affected more than 10% of the adult population. Heartwood extracts of Pterocarpus marsupium have traditionally been used to manage diabetes-like conditions. Numerous studies have been published to validate the plant extract’s potential in treating diabetes mellitus. However, studies focussing on the roles of secondary metabolites from the plant in managing diabetes are lacking. Here, we present an in silico approach to describe the antidiabetic potential of the plant metabolites we had previously isolated from 70% MeOH extracts of the heartwood of the plant. Seven compounds isolated from the plant were docked with 10 macromolecules that are known antidiabetic targets to calculate binding affinity and visualize the ligand–receptor interactions. MD simulations were conducted to investigate the dynamic behaviour and stability of protein–ligand complexes in water environment, providing insights into atomistic interactions between ligands and protein residues. In silico antidiabetic activity was predicted by the Prediction of Activity Spectra for Substances (PASS) program. The PASS application predicted that the discovered phytochemicals have antidiabetic properties. The ADME properties, toxicity profile, medicinal chemistry and drug-likeness were predicted, and the novel compound bijaysaline was found to possess good binding affinity and drug-likeliness properties.